Quantitative risk assessment of Campylobacter and its biological control of foodborne pathogens - Premarathne, Jayasekara Mudiyanselage Krishanthi Jayarukshi Kumari (2017)
Campylobacter foodborne diseases are a major current public health challenge faced by the world and often Campylobacter infections are under reported. Furthermore, reduced efficacy of antibiotics against bacterial pathogens has complicated the status of foodborne pathogens. In Malaysia, foodborne infections show an upward trend and multidrug-resistant foodborne pathogens were reported in the country. Therefore, estimation of risk and developing new alternatives for antibiotics are greatly concerned. In view of all these, the aims of this study were to determine the prevalence and concentration of Campylobacter in beef food system at farm and retail level using most probable number (MPN)-multiplex Polymerase Chain Reaction (PCR) method. Campylobacter isolates were characterized based on the antibiotic susceptibility pattern. Additionally, the multilocus sequence typing (MLST) was used for the first time in Malaysia for molecular characterization of Campylobacter. A microbiological quantitative risk assessment was conducted to estimate the potential of human campylobacteriosis in Malaysia with consumption of contaminated beef. A risk assessment model was developed based on the framework proposed by the Codex Alimentarius Commission, created in an Excel spreadsheet and was simulated using @Risk, version 5.5 (Palisade, USA). Correspondingly, bacteriophages were isolated to biocontrol Campylobacter. All isolated bacteriophages were characterized based on the morphology, host range, physiochemical properties and type of nucleic acid. Consequently, the efficacy of the isolated phages were assessed on respective host pathogens on chicken and beef meat to determine the applicability of those as bio-control measures. The prevalence of Campylobacter spp. in cattle was 33%, while raw beef purchased from local wet markets and hypermarkets were contaminated at 14.2% and 7.5% respectively. The most prevalent Campylobacter species isolated from both cattle and beef were Campylobacter jejuni (58.57%), the remainder was Campylobacter coli (27.14%) and other Campylobacter species (14.28%). The microbial load of Campylobacter on cattle and beef ranged from 3-436 MPN/g and 3-75 MPN/g respectively. The Campylobacter isolates were highly resistant to tetracycline (76.9%) and ampicillin (69.2%), whereas was susceptible to gentamicin (84.6%) and chloramphenicol (92.4%). Notably, multidrug resistance (MDR) was apparent in 53.8% of the isolates. The MLST indicated that C. jejuni and C. coli sequence types associated with human infections. The developed model simulated the contamination of beef with Campylobacter from the retail to table continuum. The model indicated that the probability of contamination of beef with Campylobacter species ranged from 0.08 to 0.14 within a 90% confidence interval. According to the model prediction, 483 cases per 100, 000 population were estimated due to consumption of contaminated beef while 0.06 cases per 100, 000 population was associated with inadequately cooked beef. The sensitivity analysis indicated that domestic food safety measures such as cross contamination, insufficient cooking temperature and washing beef can increase the risk of human campylobacteriosis. Five different virulent bacteriophages namely ØEC1, ØEC2 (E. coli), ØLM3 (L. monocytogenes), ØMRSA1 (S. aureus) and ØCC1 (C. jejuni and C. coli) were isolated from various food commodities. The samples harboured 8.1 × 1010 ± 4.02 to 4.7 × 102 ± 1.04 PFU/ml phages concentration. Morphological characteristics observed through the transmission electron microscopy (TEM) revealed that four of the isolated bacteriophages (ØEC1, ØLM3, ØMRSA1, and ØCC1) belonged to family Myoviridae while ØEC2 belonged to the Podoviridae family. The optimal multiplication of infection was observed at 0.01 for ØEC1, ØLM3, ØMRSA1 and ØCC1 bacteriophages while 0.001 for ØLM3 phage. One-step growth kinetics of the bacteriophages showed a latent period of 15 -55 mins and 10-40 mins eclipse period. The burst size of isolated bacteriophages ranged 29-185 for phage particles/infected cell. Bacteriophages ØEC1, ØMRSA1, and ØCC1 were stable between pH 5-9. However, limited pH stability was observed for ØLM3 (pH 6-8) and ØEC2 (pH 7-8). The phage ØCC1 was able to survive up to 40 °C temperature while the remainder was stable at 4-37 °C. In the efficacy study, isolated bacteriophages significantly (2-3 log10 CFU/mL, P ≤ 0.05) decreased numbers of E. coli, L. monocytogenes, and S. aureus on chicken and beef after 3 h of application. Following ØCC1 phage application to C. jejuni and C. coli contaminated chicken and beef, a significant (2-3 log10 CFU/mL, P ≤ 0.05) reduction was observed after 12 h. The host bacterial decline persisted during the experimental study and none of the host pathogens recuperated into the initial contamination levels. In conclusions, this study emphasis on the high potential risk areas to be concerned in implementing food safety decisions and provides the basis for future experiments in the utilization of bacteriophages as biocontrol agents in the food industry.